Trusted Computing in Context. - Schneider, Fred (IEEE Security and privacy : building confidence in a networked world)
The trusted computing technology embodied in the Trusted Platform Module secure-coprocessor from the Trusted Computing Group is a hardware-based root of trust that makes it possible for the system designer--not the computer owner--to regulate which programs can run on a given computer. If system designers are evil, then they can use trusted computing to prevent a competitors' programs from being installed, thus creating or preserving a monopoly. When computer owners are incompetent, though, benevolent system designers can use trusted computing to prevent malware from being installed and run.